2022
DOI: 10.3390/cancers14112772
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Exposure to Decabromodiphenyl Ether Promotes the Proliferation and Tumourigenesis of Papillary Thyroid Carcinoma by Inhibiting TRß

Abstract: Polybrominated diphenyl ethers (PBDEs) have been reported to possess endocrine-disrupting and tumour-promoting activity. However, the effects of long-term exposure to decabromodiphenyl ether (BDE209) on thyroid tumourigenesis of papillary thyroid carcinoma (PTC) and the underlying mechanisms remain poorly defined. In this study, functional assays in vitro and mouse models in vivo were used to evaluate the toxic effects of long-term exposure to environmental concentrations of BDE209 on the pathogenesis and prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…A recent in vitro and in vivo mouse model study demonstrated that long-term exposure (defined as more than 27 days) to environmental concentrations of decaBDE (BDE-209) increased the proliferation of normal human follicular epithelial cell line and papillary thyroid carcinoma (PTC)-derived cell lines [76]. Specifically, as shown in another in vitro and in vivo study, BDE-209 stimulates cell proliferation during both the S and the G2/M phases of the cell cycle, acting as a competitive inhibitor of TRß expression and function [76]. Furthermore, an in vitro study on human thyroid follicular cell lines indicated that cells exposed to PBDEs showed DNA single-stranded and double-stranded breaks [77].…”
Section: Thyroid Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…A recent in vitro and in vivo mouse model study demonstrated that long-term exposure (defined as more than 27 days) to environmental concentrations of decaBDE (BDE-209) increased the proliferation of normal human follicular epithelial cell line and papillary thyroid carcinoma (PTC)-derived cell lines [76]. Specifically, as shown in another in vitro and in vivo study, BDE-209 stimulates cell proliferation during both the S and the G2/M phases of the cell cycle, acting as a competitive inhibitor of TRß expression and function [76]. Furthermore, an in vitro study on human thyroid follicular cell lines indicated that cells exposed to PBDEs showed DNA single-stranded and double-stranded breaks [77].…”
Section: Thyroid Cancermentioning
confidence: 99%
“…Increased proliferation of normal human follicular epithelial cell line and papillary thyroid carcinoma (PTC)-derived cell lines (both in vivo and in vitro) [76]. Cell proliferation stimulus (both in vivo and in vitro) [76].…”
Section: Pubertal Effects Ovarian Function and Reproductive Healthmentioning
confidence: 99%